2023
DOI: 10.3390/su151310239
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Odd Beta Prime-Logistic Distribution: Desirable Mathematical Properties and Applications to Engineering and Environmental Data

Abstract: In parametric statistical modeling, it is important to construct new extensions of existing probability distributions (PDs) that can make modeling data more flexible and help stakeholders make better decisions. In the present study, a new family of probability distributions (FPDs) called the odd beta prime generalized (OBP-G) FPDs is proposed to improve the traditional PDs. A new PD called the odd beta prime-logistic (OBP-logistic) distribution has been developed based on the developed OBP-G FPDs. Some desirab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 71 publications
(87 reference statements)
0
3
0
Order By: Relevance
“…Meanwhile, another study in India found that the normal distribution gives the best fit, followed by Log-normal and Gamma distributions to model the annual maximum temperature [24]. In a separate study conducted in Nigeria, it was determined that for modeling the groundwater pollutant concentrations, the odd beta prime Fréchet distribution provided the most accurate fit [77].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, another study in India found that the normal distribution gives the best fit, followed by Log-normal and Gamma distributions to model the annual maximum temperature [24]. In a separate study conducted in Nigeria, it was determined that for modeling the groundwater pollutant concentrations, the odd beta prime Fréchet distribution provided the most accurate fit [77].…”
Section: Discussionmentioning
confidence: 99%
“…A similar study was conducted to evaluate the chemical parameters of groundwater using six probability distributions, such as normal, log-normal, gamma, Weibull, logistic, and log-logistic distributions [33]. The following studies can be referred to for more probability distribution modeling works [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“…These observations further support the novelty and significance of the proposed model. Recent literature has introduced several univariate distributions, such as those in [30][31][32], which often possess complex structures that can complicate their practical use. In contrast, the B-SIOR-G model, described in Equation ( 2), maintains a relatively simple structure.…”
Section: Introductionmentioning
confidence: 99%
“…The extension of well-known distributions for modeling real data via generalized classes of distributions has received considerable attention during the last decade. In particular, the recent distributions proposed using the T-X approach include the exponentiated odd Lindley-X family by [7], the Maxwell-Weibull distribution by [8], the Maxwell-Lomax distribution by [9], the Maxwell-exponential distribution by [10], the odd beta prime-G family by [11], the odd beta prime-logistic distribution by [12], the odd beta prime-Fréchet distribution by [13], the log-Topp-Leone distribution by [14], and more others.…”
Section: Introductionmentioning
confidence: 99%